Administrative control authority in maintaining public health under exceptional circumstances (Corona Model) - et. al., Ramzi Mahmoud Nayef Hilat, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Due to the spread of the Coronavirus epidemic, the competent public authorities resorted to taking a number of preventive measures to limit and combat its spread, and these measures varied between restricting some freedoms, especially freedom of movement and assembly, economic freedom and organizing public facilities in order to adapt to the situation and limit the spread of the epidemic. The most important measures taken by the administrative control authorities are to close some commercial activities, disrupt transportation, home quarantine, and obligate community distancing, while following these and other measures with administrative and penal sanctions until it is respected, and this study aims to address the measures taken to limit the spread of the Coronavirus epidemic. By the administrative control authorities and how they are successful in fighting this epidemic. And the extent of judicial oversight of the actions of these authorities during the pandemic.